DISCIPLINE AND PROFESSIONAL DEVELOPMENT AS PROGNOSTICATORS OF STUDENT'S ACADEMIC ACHIEVEMENT IN MATHEMATICS - Oyenike, OSHIN; Oluwafunmilayo , OLANIRAN; Abraham, OKETUNBI; Adenike, AFOLABI (African Journal of Education and Practice, 2022)
Purpose: Underperformance of secondary school students in Mathematics is a great concern to all stakeholders in education sector. Efforts have been made by many researchers to arrest this situation, but it seems unresolved. Therefore, this study examined discipline and professional development as prognosticators of student's academic achievement in mathematics. The study was led by four hypotheses and relevant literatures were reviewed. Methodology: Survey research design was used, and the population comprised all secondary schools in South-West Nigeria. Multistage sampling technique was employed: Simple random sampling technique was used to select three (3) out of the six (6) states in South-West, five (5) Local Government Area (LGA) from each state and from each LGA ten (10) schools and 10 students from each school was selected. In all 3 states, 15 LGA, 150 schools and 1500 students were used. Also, purposive sampling method was used to select two (2) teachers of Mathematics from each school. Thus, a total of three hundred (300) teachers of Mathematics were used for the study. Data collection was done by using Discipline and Professional Development Questionnaire (DPDQ) and Mathematics Achievement Test(MAT) with reliability coefficients of 0.82 and 0.86 respectively and content and face validity of the instruments was established by expert in test construction. Findings: The findings clearly revealed discipline and professional development as prognosticators of secondary school students'achievement in mathematics. It can be concluded that the two predictor variables are effective in improving students'academic achievement in Mathematics. Unique contribution to theory, practice and policy: This investigation has generated baseline data about the importance of discipline and professional development in schools. It was recommended that eenlightenment programmes should be organized on what should constitute the disciplinary measures to take in schools to improve students' achievement in Mathematics. When correcting misbehaviour educators should focus on strategies for developing self-discipline and for preventing misbehaviour. There should be regular training and re-training programmes for teachers in schools so as to provide a basis for their own personal improvement with regards to knowledge in their areas of study and, by extension, improvement on the performances of their students. A relevant theory is the Glasser Theory of Classroom Management is based on the principles that the classroom environment and curriculum should create a safe place for learning by meeting the needs for belonging, power, fun and freedom (William 2009) . Glasser also stressed helping the students achieve success by teaching them to make appropriate behavioural choices. According to Glasser, behaviour is a matter of choice. A student's behaviour stems from the choices he or she makes. It's the teacher's responsibility to help the students make good choices, which would result in good behaviour.The Glasser Theory states that teachers should stress student responsibility, establish rules that lead to success, accept no excuses, call for value judgments, suggest suitable alternatives, invoke responsible consequences, be persistent, and carry out continual review. The benefit Glasser believed that students will have is that they will be provided with a choice in deciding the curriculum and classroom rules. This will help the students take ownership of the learning process, leading to increased enthusiasm, confidence and participation. Teachers employing the Glasser Theory may need to deviate from the classical classroom structure in order to achieve success. Glasser favours having the students work together in small groups. This fosters a sense of belonging, motivates the students to work for the group, and reduces theirdependence on the teacher. When divided into smaller groups, stronger students will help the weaker students, improving relationships and classroom harmony.The Glasser Theory alone won't eliminate all classroom behavioural problems however. Glasser suggests that the teacher organizes the classroom the best way possible to meet students' needs and then intervene with the supplied strategies to improve behaviour (William, 2009). Even when the theory is followed, Glasser concedes up to 25 percent of students may remain unproductive. This theory therefore cannot be the best for this study. Kohn's theory of classroom management emphasises curiosity and cooperation above all else. This is true throughout Kohn's discussions on standards, standardized testing, homework, and classroom management. Kohn believes that the students' curiosity should govern what is taught inside the classroom